On the possible role of ERK, p38 and CaMKII in the regulation of CGRP expression in morphine-tolerant rats - Quirion Remi; Chabot Jean-Guy; Wang Zhiyong (SAGE Publishing, 2011)
Abstract Background The neuropeptide, calcitonin gene-related peptide (CGRP) has been proposed to be a regulator of the development of morphine analgesic tolerance and thereby could be a target to reduce the induction of this phenomenon under clinical conditions. However, the mechanisms of CGRP regulation are unclear. We investigated here the possible role of the extracellular signal-regulated protein kinase (ERK), p38 and calcium/calmodulin-dependent protein kinase II (CaMKII) in CGRP regulation following chronic morphine treatment. Results A 7-day treatment with morphine (15 μg/day) led to an increase in CGRP contents in the spinal cord dorsal horn (SCDH) and dorsal root ganglion (DRG) and this effect was prevented by the inhibition of the ERK, p38 or CaMKII pathway. The phosphorylation/activation of ERK, p38 and CaMKII was enhanced in the SCDH following chronic morphine while in DRG only the phosphorylation of CaMKII was increased. Moreover, our chronic morphine treatment up-regulated neuronal nitric oxide synthase (nNOS) levels in the SCDH, an effect blocked by the inhibition of the ERK, p38 or CaMKII pathway. The blockade of nNOS activity also suppressed chronic morphine-induced CGRP increases in the DRG and SCDH. Double immunofluorescence studies revealed that nNOS and CaMKII are co-localized in the SCDH and that CaMKII is activated in CGRP-expressing DRG neurons. Conclusions The activation of spinal ERK, p38 and CaMKII, alongside nNOS, is involved in chronic morphine-induced CGRP up-regulation in both the DRG and SCDH. Moreover, the stimulation of CaMKII in the DRG likely directly regulates the expression of CGRP associated with morphine analgesic tolerance.